Effect of a ciliary neurotrophic factor polymorphism on schizophrenia symptom improvement in an iloperidone clinical trial. (March 2008) - Lavedan, Christian; Volpi, Simona; Polymeropoulos, Mihael H; Wolfgang, Curt D
Aims: Presence of the null FS63TER allele of the rs1800169 polymorphism in the gene encoding the ciliary neurotrophic factor ( CNTF ) may increase the risk of schizophrenia. This study prospectively evaluated the CNTF rs1800169 genotype (G/G vs non-G/G) effects on response to iloperidone.Patients & Methods: Iloperidone 24  mg/day was evaluated in a study of patients with schizophrenia. Efficacy measurements included Positive and Negative Syndrome Scale total (PANSS-T), Brief Psychiatric Rating Scale (BPRS) and Clinical, Global, Impression (CGI) scores. The step-down primary end point was the difference in PANSS-T scores based on CNTF rs1800169 G/G genotype.Results: This study genotyped 417  patients (279 iloperidone and 138 placebo) for the rs1800169 polymorphism. Iloperidone significantly improved PANSS-T, PANSS positive subscale (PANSS-P), PANSS negative subscale (PANSS-N), BPRS, Clinical Global Impression of Change (CGI-C) and Clinical Global Impression of Severity (CGI-S) scores versus placebo. G/G versus non-G/G patients had greater improvement with iloperidone versus placebo in PANSS, BPRS and CGI scores.Conclusions: The relative treatment benefit of iloperidone compared with placebo in patients with schizophrenia is enhanced in patients homozygous G/G for the rs1800169 polymorphism.